New paleomagnetic pole for the Upper Jurassic Chon Aike Formation of southern Argentina (South America): Testing the tectonic stability of Patagonia with respect to South America, and implications to Middle Jurassic-Early Cretaceous true polar wander - Ruiz González, Víctor (2019)
Fil: Ruiz González, Víctor. Universidad de Buenos Aires. Instituto de Geociencias Básicas, Aplicadas y Ambientales de Buenos Aires. Buenos Aires, Argentina.